2003
DOI: 10.1177/00187267035611002
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Yet Significant: The Existence and Impact of Everyday Racial Discrimination in the Workplace

Abstract: In this article, we argue that research concerning workplace discrimination could be advanced by considering ‘everyday discrimination,’ that is, the subtle, pervasive discriminatory acts experienced by members of stigmatized groups on a daily basis. Three studies are reported which use secondary data analysis techniques to provide evidence for the existence of everyday workplace discrimination against Blacks. In addition to demonstrating the occurrence of such discrimination, evidence is presented which indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
370
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(392 citation statements)
references
References 50 publications
(73 reference statements)
16
370
2
4
Order By: Relevance
“…Yet, this open rejection of individuals based on their group membership is increasingly becoming a thing of the past (cf. Coenders, Scheepers, Sniderman, & Verberk, 2001;Deitch et al, 2003;Meertens & Pettigrew, 1997), as discrimination is legally forbidden in many Western countries and publicly spurned.…”
Section: Discrimination Subtle Discrimination and Boundariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, this open rejection of individuals based on their group membership is increasingly becoming a thing of the past (cf. Coenders, Scheepers, Sniderman, & Verberk, 2001;Deitch et al, 2003;Meertens & Pettigrew, 1997), as discrimination is legally forbidden in many Western countries and publicly spurned.…”
Section: Discrimination Subtle Discrimination and Boundariesmentioning
confidence: 99%
“…Subtle discrimination can be understood as behaviour "…entrenched in common, everyday interactions, taking the shape of harassment, jokes, incivility, avoidance, and other types of disrespectful treatment" (Van Laer & Janssens, 2011, p. 1205. It pervades everyday situations and is characterized by covertness (Meertens & Pettigrew, 1997), occurring specifically in situations in which perpetrators can "hide" their intentions, maintaining the image of being non-discriminatory (Ellemers & Barreto, 2009;Deitch et al, 2003;Van Laer & Janssens, 2011). This makes subtle discrimination difficult to recognize and address when on the receiving end of it.…”
Section: Discrimination Subtle Discrimination and Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps even more telling is that a similar proportion of respondents in that study indicated that they had seen a coworker harassed based on their ethnicity suggesting that this covert form of activity does not appear to be taboo. Though this type of mistreatment is more difficult to prove in court and, arguably, harder for an employer to control, it is important to recognize that it too has a considerable negative impact on the well being of those who are unfortunate enough to experience or even witness it (e.g., Deitch et al 2003;Low et al 2007;Wang et al 2011). …”
Section: Discrimination Has Evolvedmentioning
confidence: 99%
“…Eksempelvis har kønsstudier fokuseret på køn-sidentiteter og hvordan de skabes i organisationer (fx Adkins, 1995;Wilson, 1996;Townsley, 2003), ligesom etnisk herkomst og seksualitet har fået opmaerksomhed i organisationsforskningen (fx Deitch et al, 2003;Ward & Winstanley, 2003). Det skaerpede fokus på menneskelige relationer i organisationer, som vi har oplevet i den seneste tid, har ansporet en ny organisationsforskning, som fokuserer på identitetsarbejde og magtforhold (fx Casey, 1999;Trethewey, 1999;Alvesson & Willmott, 2002;Merilainen et al, 2004;Ball, 2005;Hoobler, 2005;Mik-Meyer, 2009, 2010aMik-Meyer & Villadsen 2012).…”
Section: Aims and Scopesunclassified